Investigating freshmen’s L2 speaking anxiety level in Indonesia - Emeral; Ristati (English Language Education Study Program of STKIP PGRI Banjarmasin, 2023)
The present study aims at investigating freshmen’s English (hereafter is called L2) speaking anxiety level in the classroom. The data were derived from online survey on 155 freshmen on two English Education Departments in Palangka Raya. The result indicated that the freshmen were experiencing a high level of L2 speaking anxiety in the classroom. Further, the result of independent sample t-test analysis showed that there was no significant difference on freshmen’s L2 speaking anxiety level by their gender. Similarly, one-way ANOVA analysis indicated that there was no a statistical difference on freshmen’s L2 speaking anxiety by English learning experience. Considering the findings, a high level of speaking anxiety is a serious problem to measure as it will make students disinclined to L2 speaking activities leading to poor L2 speaking fluency.